Seminar dan Pelatihan Dasar Public Speaking sebagai Interpersonal Skill Siswa SMK Saintek Nurul Muslimin - Ririn Uke Saraswati; Suripto Moh. Zulkifli; Satim Hamid; Vina Aprilia Anjani; Rizky Ramadhan; Fatimah Az-Zahra; Muhammad Arif Febriyanto; Muhamad Daman Ardian (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Public speaking is one of the essential interpersonal skills that must be possessed to compete in both the professional and entrepreneurial world, especially for the younger generation. Based on observations, many students still lack confidence when speaking in public, including students of SMK Saintek Nurul Muslimin. The seminar and training activity themed "Enhancing Understanding of Public Speaking as an Interpersonal Skill for the Young Generation Entering the Workforce and Entrepreneurship" aims to improve participants' understanding of the importance of public speaking as an interpersonal skill and equip them with effective public speaking techniques. The implementation method includes a seminar and training on the significance of interpersonal skills and how to become a good public speaker. Beyond theory, participants also have the opportunity to directly practice basic public speaking techniques and engage in role-playing with the speakers. This activity was conducted at SMK Saintek Nurul Muslimin and attended by 76 participants, comprising 12th-grade students from several schools in Batujaya Subdistrict and members of the general public. The results of this seminar and training indicate that participants were able to enhance their confidence in applying public speaking skills